Dialysis Outcomes Among Elderly Populations in Asian Countries - Evsanaa, Baigalmaa; Damdinsuren, Khurtsbayar; Dagvasumberel, Munkhbaatar; Togtokh, Ariunaa (Central Asian Journal of Medical Sciences, 2017)
The inevitable reality of today is that the world population is aging, and the elderly (above 65 years) are more prevalent among the dialysis population worldwide. Objectives: The purpose of this review is to do a literature search on issues related to dialysis in the elderly Asian population, such as vascular access outcomes, complication rates, and survival data by modality on hemodialysis (HD) and peritoneal dialysis (PD). Methods: A literature search on key topic areas was done on articles published in English between January 1, 2005 and December 31, 2015. Results: Although incidences of elderly dialysis patients are increasing in Asia, we found that large-scale data is lacking. Further research is needed to assess dialysis outcomes among the elderly. Available studies suggest acceptable outcomes in vascular access, primary and secondary patency rates, and similar intervention rates compared to non-elderly. Survival data suggests superior outcomes in HD in elderly. Due to significant differences in dialysis practices in Asia, a proper comparison is difficult. Conclusion: Age alone is not a contraindication for dialysis.